Faktor risiko gizi buruk pada balita di Kabupaten Donggala Provinsi Sulawesi Tengah - Eka Prasetia Hati Baculu; M Juffrie; Siti Helmyati (Alma Ata University Press, 2015)
ABSTRACTBackground: Severe malnutrition is a state of severe malnourished condition caused by low consumption of energy and protein in a long time. Severe malnutrition interferes the children growth and development, moreover malnourished children are vulnerable to get infectious diseases, even the death.Objectives: To analyze the risk factors of severe malnutrition among children under five in Donggala, Central of Sulawesi Province.Methods: This study used case-control (observational study). The study was conducted in District Dampelas Donggala on July to September 2014. The population was all children underfive selected by total sampling method. The samples were 64 children aged 0-59 months which separated into 2 groups,case and control group.The independent variables were the level of energy intake of protein, parenting, and infectious diseases, while the dependent variable was the incidence of severe malnutrition among children under five. Data were obtained by direct interview using questionnaire and recall 24 hours to determine the level of energy and protein intake. The data collected were analyzed using univariate analysis (descriptive), bivariate (chi-square), and multivariate (multiple logistic regression).Results: The result of this study based on the bivariate analysis presented that the level of energy intake (OR=9.86, 95% CI:3.49-27.89), infectious disease (OR=2.83, 95% CI:1.10-7.31), and as low birth weight external variables (OR=5.76, 95% CI:1.43-23.20) signifi cantly associated with the incidence of severe malnutrition. There were no significant association between the level of protein intake (OR=1.18, 95% CI:0.47-2.92) and parenting (OR=1.21, 95% CI:0.50-2.92) with the incidence of severe malnutrition. In the other hand, based on multivariate analysis by controlling the variable of low birth weight history, this study’s result presented that the level of energy intake had the strongest association with the risk of incidence of severe malnutrition compared to the other variables.Conclusions: The level of energy intake and infectious disease were the risk factors for the incidence of severe malnutrition among children under five, while the level of protein intake and parenting were not.KEYWORDS: children underfive, energy, infectious disease, parenting, protein, severe malnutritionABSTRAKLatar belakang: Gizi buruk adalah keadaan kurang gizi tingkat berat yang disebabkan oleh rendahnya konsumsi energi dan protein dalam waktu cukup lama. Kekurangan gizi selain mengganggu pertumbuhan dan perkembangan, dapat pula mengakibatkan balita rentan terhadap penyakit infeksi bahkan dapatmenyebabkan kematian.Tujuan: Untuk menganalisis faktor risiko kejadian gizi buruk pada balita di Kabupaten Donggala, Provinsi Sulawesi Tengah.Metode: Jenis penelitian ini observasional dengan rancangan case-control. Penelitian dilakukan di Kecamatan Dampelas, Kabupaten Donggala pada bulan Juli sampai September 2014. Populasi adalah semua balita dan sampel ditentukan dengan metode total sampling. Balita usia 0–59 bulan yang berjumlah 64 dimasukkan pada masing-masing kelompok kasus dan kontrol. Variabel bebas yaitu tingkat asupan energi protein, pola asuh, dan penyakit infeksi sedangkan variabel terikatnya adalah kejadian gizi buruk pada balita. Data diperoleh dengan wawancara langsung menggunakan kuesioner dan recall 24 jam untuk mengetahui tingkat asupan energi dan protein. Data dianalisis dengan analisis univariat (deskriptif), bivariat (chi-square), dan multivariat (regresi logistik berganda).Hasil: Hasil analisis bivariat menunjukkan bahwa tingkat asupan energi (OR=9,86, 95% CI:3,49-27,89), penyakit infeksi (OR=2,83, 95% CI:1,10-7,31), dan variabel luar BBLR (OR=5,76, 95% CI:1,43-23,20) berhubungan signifikan dengan gizi buruk. Tidak ada hubungan yang signifikan antara tingkat asupan protein (OR=1,18, 95%CI:0,47-2,92) dan pola asuh (OR=1,21, 95%CI:0,50-2,92) dengan gizi buruk. Hasil analisis multivariat dengan mengendalikan riwayat BBLR menunjukkan bahwa tingkat asupan energi memiliki hubungan kuat dengan risiko kejadian gizi buruk dibandingkan variabel lainnya.Kesimpulan: Tingkat asupan energi dan penyakit infeksi merupakan faktor risiko kejadian gizi buruk padabalita, sedangkan tingkat asupan protein dan pola asuh bukan merupakan faktor risiko.KATA KUNCI: balita, energi, penyakit infeksi, pola asuh, protein, gizi buruk, gizi